Improved polyacrylate fiber manufacturing process and uses thereof
By optimizing reaction conditions and parameters in the production of polyacrylate fibers, including the use of alternative crosslinking agents and continuous industrial processes, the inefficiencies and environmental impacts of current methods are addressed, resulting in reduced energy and water consumption and lower production costs.
Patent Information
- Application Number
- JP2024556053
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-02-13
- Publication Date
- 2025-04-15
AI Technical Summary
Current methods for producing polyacrylate fibers are inefficient, requiring long reaction times, high energy and water consumption, and resulting in high production costs and environmental impact.
Optimization of reaction conditions and parameters in the production process of polyacrylate fibers, including the use of alternative crosslinking agents with multiple amine functional groups, reduced reaction times, and implementation of continuous industrial processes to minimize water and energy usage.
The optimized process significantly reduces energy and water consumption, decreases production time, and lowers manufacturing costs, while also enhancing the environmental sustainability of the polyacrylate fiber production process.
Smart Images

Figure 2025510709000001 
Figure 2025510709000002 
Figure 2025510709000003
Abstract
Description
[Technical field]
[0001] The present invention provides a process developed and optimized in the related art for producing polyacrylate fibers from acrylic fibers. The present invention relates to the optimization of reaction conditions and parameters of process steps in existing processes for producing polyacrylate fiber products. In the polyacrylate production process of the present invention, by finding the ideal reaction conditions and parameters, it is possible to increase production capacity, reduce cycle costs and energy consumption, and increase efficiency. Furthermore, the improvements made in the production process of the present invention allow for the reduction of water consumption used during the production of polyacrylate fibers, the resulting carbon footprint, and the minimization of the generation of waste by-products, thereby resulting in environmentally friendly and sustainable polyacrylate fibers.
[0002] The present invention relates to the creation of an efficient process by optimizing reaction environment conditions and parameters for the production of polyacrylate fibers, which mainly belong to the textile field and are involved as raw materials in the production of textile products with many different functions, and the industrial applicability of this process. [Background technology]
[0003] Acrylic fibers are obtained in various thicknesses and crossed forms as a result of converting homopolymers or copolymers containing 85% by weight or more of acrylonitrile monomer into solution form with the aid of at least one solvent, and then applying wet / dry methods known in the art from these solutions. During the applied process steps, additional methods can be developed or chemicals can be added to improve the chemical-physical properties and performance to obtain acrylic fiber products that are suitable for the needs and sectors of the consumer. Acrylic fibers are a type of fiber that is frequently used in the art in relation to being washable as synthetic fibers, not retaining their shape, providing insect, oil and chemical resistance, being colored, and having high fastness properties to sunlight and heat as synthetic fibers.
[0004] Due to its components, polyacrylate fibers are resistant to heat and flame, have a low heat transfer coefficient, high thermal insulation and moisture absorption, and also have high odor adsorption due to chemical resistance to acidic and basic, pH-balanced buffers, and acidic, cationic and reactive paint systems. Due to the above characteristics, polyacrylate fibers are a type of fiber that is frequently used in the related technical field. Polyacrylate fibers are obtained from acrylic fibers by methods known in the art. The manufacturing method includes the following process steps: -Chemical cross-linking reaction of acrylic fibers. The use of multi-amine functional chemicals used as crosslinkers in this process step requires high safety and process control due to their corrosive chemical action, carcinogenicity, skin itching, sensitive effects, environmental aquatic toxicity, and strong reducing, extremely explosive and flammable properties. -Hydrolysis reaction of nitrile groups in the fiber with metal alkali salts. As is known, this process step is essentially a two-step reaction mechanism of attachment and removal. In the related art, this process step involves the nitrile group, -CONH2, -COO-M +It has been found that conversion does not occur with 100% efficiency and this negative situation affects process parameters and conditions and therefore product quality. The resulting fibers are subjected to a neutralization reaction. As a result of applying the previous process steps, strongly basic carboxylate salts are obtained, and to achieve a high efficiency of the subject neutralization process, it is necessary to select the most suitable acid and to optimize the process step conditions. As a final process step, a polyvalent metal complex formation process is carried out. In this process step, it is important to select an appropriate solvent for the metal organic-inorganic salt, determine the process step conditions that will result in the desired amount of ionization, and determine the parameters that will form the chelate complex coordinate bonds of the metal ions.
[0005] In this technology, the production of polyacrylate fiber is carried out by applying the above four independent reactions. The process of the current technology applied to the production of polyacrylate fiber is a discontinuous and inefficient production method due to the long reaction time, complex reaction mechanism, and precise production process steps. This negative situation faced in the current technology increases the production cost, time, energy, and water loss of polyacrylate fiber. Instead of all these negative production processes, a production method that can perform high-efficiency and continuous industrial production and eliminate the existing shortcomings has become a must for the related technical field.
[0006] WO 2008 / 128660 relates to a process for producing fire-resistant polyacrylate fibres that are low in toxicity, have low smoke emissions and are uniformly dyed. The process of the invention comprises the following process steps: A hydrazine solution with a concentration of -15% by weight is used as the crosslinking agent for the acrylic fibers, and the crosslinking process is carried out at a temperature of 105°C for 5 hours. The next treatment step is neutralization with a 5% strength by weight sodium hydroxide solution, this treatment step being carried out at a temperature of 100° C. for 2 hours. - Then a neutralization process is carried out with a sulfuric acid solution of 5% by weight concentration, this process step being carried out at a temperature of 60°C for 1 hour. - The final process step is the formation of a complex with the treated solution from a mixture of zinc acetate and acetic acid, this process is carried out at a temperature of 100°C for 1 hour.
[0007] In this invention, very complex and controllable process steps are applied to obtain polyacrylate fibers with the desired properties, but the process steps have long reaction times. In this invention, it takes at least 9 hours to obtain polyacrylate fibers. It is clear that such a long reaction time production process requires large energy, labor, and water requirements, resulting in high costs and controllability for the production of polyacrylate fibers.
[0008] The invention of EP 1 788 145 A1 relates to a fiber with high flame retardancy and moisture absorption properties and its manufacture. To obtain a fiber with the above mentioned properties, the following process steps are applied: A hydrazine solution is used to crosslink the fibers, the crosslinking solution comprising 30% by weight of hydrazine solution, and this process step is carried out at a temperature of 98°C for 3 hours. - For the hydrolysis process, a sodium hydroxide solution with a concentration of 3% by weight is used, this process step being carried out at a temperature of 92°C for a period of 5 hours. For the neutralization treatment, a nitric acid solution having a concentration of 6% by weight is used, this process step being carried out at a temperature of 60° C. for a period of 2 hours. In the complexation process, a magnesium nitrate solution with a concentration of 15% by weight is used, and this process step is carried out at a temperature of 60° C. for 2 hours.
[0009] In order to produce fibers having the desired properties in this invention, the aforementioned reactive process steps must be applied for at least 12 hours at the specified temperatures and ingredients.
[0010] The invention of EP 1 026 309 A1 relates to obtaining fibers that have flame retardant properties and can be used as raw materials or fillers in clothing, upholstery, transport and construction. To obtain said fibers, the following process steps are applied: - A hydrazine solution is used to crosslink the fibers, the crosslinker solution comprises the use of a 35% by weight hydrazine solution, this process step is carried out at a temperature of 120°C for 2 hours. - For the hydrolysis process, a sodium hydroxide solution with a concentration of 32% by weight is used, this process step being carried out at a temperature of 120°C for a period of 0.5 hours. For the neutralization process, a nitric acid solution with a concentration of 5.8% by weight is used, this process step being carried out at a temperature of 65°C for 2 hours. In the complexation process, a zinc sulfate solution with a concentration of 13% by weight is used, and this process step is carried out at a temperature of 120° C. for a period of 20 minutes.
[0011] In order to produce fibers having the characteristics desired in this invention, a reactive process step must be applied at the specified temperature and ingredients for at least 5 hours.
[0012] The production of polyacrylate fibers by methods known in the art results from the application of process steps over a period of 5 to 24 hours. The lengthy process times for the production of polyacrylate fibers result in increased consumption of energy, water and chemical inputs, reduced process efficiency, work density and excessive manpower requirements. This makes testing, research and development processes essential to make the polyacrylate fiber production process more environmentally friendly and to reduce unit production costs. Detailed Description of the Invention
[0013] The present invention provides a method for optimizing and improving the process steps for producing polyacrylate fibers in order to eliminate the known shortcomings in the related art and to provide further advantages in the art, with the aim of obtaining a more environmentally friendly, high throughput, controllable, continuous industrial process for producing polyacrylate fibers.
[0014] The method of the present invention applied to producing polyacrylate fibers provides technical solutions and advantages in the relevant technical field: - producing a larger amount of polyacrylate fibers per unit time, -Reduces energy consumption; -Reducing staffing needs; - Reduces consumption of water and chemical inputs; -Reducing the carbon footprint during manufacturing; -Providing a continuous industrial process; - Use chemicals that are less harmful to health, safety and the environment.
[0015] As an advantage to all of this, the present invention offers a method for producing polyacrylate fibers in a lower cost and more environmentally friendly manner.
[0016] The present invention provides a method for producing polyacrylate fibers that reduces the reaction time by implementing the optimization of reaction medium and parameters in the production of polyacrylate fibers known in the art. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] The subject of the present invention is a process developed for the production of polyacrylate fibers, the parameters of which have been optimized and which is illustrated by means of examples which do not have any limiting effect, solely for a better understanding of the subject.
[0018] In the present invention, the optimization process is applied in all process steps for producing highly efficient polyacrylate fibers, where the existing shortcomings are eliminated and the optimization process is applied in all process steps. Thus, the production method of the present invention includes the following process steps: i. crosslinking the acrylic fibers with at least one crosslinking agent; ii. subjecting the acrylic fiber fibers that have been subjected to the crosslinking process to a hydrolysis reaction with at least one metal alkali salt; iii. after process step ii, subjecting the fibers to a neutralization reaction with at least one acid; iv. The fibers resulting from the neutralization process are complexed with at least one metal salt.
[0019] Process step i) of the manufacturing method of the present invention ensures that the polymeric nitrile (-CN) groups forming the acrylic fiber are crosslinked with functional groups in the crosslinking chemical compound, preserving the fiber shape and properties during subsequent reaction steps.
[0020] A hydrazine compound may be used as a cross-linking agent in process step i) of the preparation method of the present invention.
[0021] As known in the art, hydrazine chemistry has environmental and biological disadvantages. Due to the known shortcomings of hydrazine chemistry in the art, chemical compounds having at least two or more amine chemical functional groups, at least three, four, five, or more than five, can also be used as crosslinkers in the manufacturing method of the present invention.
[0022] The crosslinker may include at least one amine functional group therein. The crosslinker may be of tertiary structure, so long as it includes at least two amine groups, or at least two amine groups with at least two, or more than three, four, five, or more than five amine chemical functional groups. Each amine group may be of primary, secondary, tertiary chemical structure, or at least two amine groups with at least two primary or secondary structures. Other chemical structures may include more than two secondary amine groups, or three, four, or five secondary amine groups, and two or more amine groups each being primary or secondary. Multiamines have a 2NH-R-NH2 structure with functional groups, where R may be an alkyl or aryl group, or may include two or more heteroaryl groups. In some chemical structures, the alkyl, aryl, or heteroalkyl groups may be linear, branched, cyclic, or may have two or more of these structures. The R group may be an ether, diether, and polyether (((CH2CH2)O) n (CH2CH2) (n=1, 2, 3, 4, 5 or more than 5), polyethoether ((CH2CR2)S)O(CH2CH2) (n=1, 2, 3, 4, 5 or more than 5), polyamine (CH2CH2)NX) n (CH2CH2), where each X is independently H or alkyl or aryl or another suitable group and n=1, 2, 3, 4, 5 or greater than 5. The R group is a pigment having chemical groups that absorb light in the visible range (400-700 nm) to impart the desired color to the fiber. The R group may be selected from flame retardant or flame retardant phosphorus chemical functional groups. These may be trialkylphosphines, trialkylphosphites, trialkylphosphates, trialkylphosphonates, trialkylphosphoramides, hexaalkylcyclotripolyphosphazines, or other phosphorus containing groups.
[0023] The method for producing the polyacrylate of the present invention may include, as a crosslinker, a chemical compound having the following formula: -NH2-(CH2) n -NH2, where n is one of the values 0, 2, 4, 6, 8; -NH2-(CH2) n -NH-(CH2) n -NH-(CH2) n -NH2, where n is one of the values 0, 2, 4, 6, 8; -NH2-(CH2) n -N-(-(CH2) n -NH2))(CH2) n -NH2, where n is one of the values 0, 2, 4, 6, 8; -NH2-(CH2) n -R-(CH2) n -NH-(CH2) n -NH2, where n is one of the values 0, 2, 4, 6, 8, and R includes one of the following groups: CH, C.
[0024] In the process of the present invention, at least one crosslinking agent containing an amine functional group can be used as the crosslinking agent.
[0025] In the manufacturing method of the present invention, a number of chemical compounds can be used as cross-linking agents. At least one of the cross-linking agents that can be used in the present invention is a chemical compound that contains an amine group.
[0026] In the present invention, a cross-linking agent is preferably used, which contains at least one amine group in its body.
[0027] A preferred embodiment of the present invention is that the crosslinker used in preparation step i) contains two or more amine functional groups therein. The crosslinker may contain two, three, four or five amine groups.
[0028] The most specific embodiment of the present invention may include as a crosslinking agent at least one of hydrazine, hexamethylenediamine, diethylenetriamine, tetraethylenetriamine, tetraethylenepentamine, bis-hexamethylenediamine, tris(2-aminoethyl)amine compounds, a mixture thereof in a specific ratio, or all of them.
[0029] The crosslinking process in process step i) is carried out under reflux conditions at boiling temperature. The process temperature in question is between 100°C and 110°C. The process temperature is preferably any one of 100°C, 105°C, 106°C, 107°C, 108°C, 109°C and 110°C.
[0030] In the process step i), the weight ratio of crosslink to acrylic fiber during crosslinking is one of 1:1, 1:25, 1:50, 1:100, 1:200, 1:300.
[0031] The crosslinker in process step i) is used to form a solution in at least one solvent. The amine groups capable of solvent bridging can be an organic solvent. The solvent includes at least one of the following organic solvents: water, methanol, ethanol, isopropanol, acetone, dimethylsulfoxide, dimethylformamide, dimethylacetamide. Preferably, water is used as the solvent, and preferably there is at least one organic solvent in the water. Preferably, there is at least one organic solvent dissolved in the water in the range of 10% to 50% by weight. In the most preferred embodiment, only water is present as the solvent. The crosslinker used in process step i) is preferably contained in the solvent at any value in the range of 20% to 60% by weight. Preferably, the crosslinker:solvent ratio is in the range of 35% to 50%.
[0032] The mixing process i) is preferably carried out within a process step. The mixing is preferably in the range of 100-500 rpm. The mixing process is preferably in the range of 200 rpm-400 rpm.
[0033] In the process step i) of the present invention, the crosslinking ratio for the acrylic fibers is 4.6% by weight (w / w). This value is considered to be the value achieved by the crosslinking required in the current state of the art. In the present invention, the crosslinking ratio for the acrylic fibers achieved in the process step i) is at least 4.6% by weight (w / w).
[0034] The reaction time of process step i) varies between 10 and 45 minutes depending on the optimization and development process.
[0035] The reaction time of process step i) is preferably in the range of 15 min to 30 min when optimization and development processes are carried out.
[0036] As known in the art, in process step ii) the polymeric nitrile (-CN) groups forming the remaining acrylic fibers, which are not involved in the crosslinking as a result of process step i), are converted to the CONH2, COOM functional groups of the nitrile groups by a two-step adhesion and elimination reaction in the presence of a metal alkali. Process step ii) is carried out under reflux reaction conditions. Preferably, process step ii) is carried out at any value within the temperature range of 100-110°C. The temperature of process step ii) is preferably any one of 100°C, 105°C, 106°C, 107°C, 108°C, 109°C and 110°C.
[0037] The reaction referred to in process step ii) is preferably carried out by mixing in at least one mixer, preferably at a speed in the range of 200-400 rpm.
[0038] The metal alkali salt referred to in process step ii) is at least one of the following compounds: calcium hydroxide, magnesium hydroxide, calcium hydroxide, sodium hydroxide, calcium nitrate, magnesium nitrate, potassium nitrate, sodium nitrate.
[0039] The metal alkali salt used in process step ii) is in the range of 8% to 20% by weight in at least one solvent. As the solvent mentioned in this specification, at least one of water, methanol, ethanol, isopropanol, solvent can be used. When water is used as the solvent and is preferred, at least one organic solvent can be present in the water. Preferably, process step ii) includes at least one solvent dissolved in water at any value in the range of 10% to 50% by weight.
[0040] In a most preferred embodiment, water is used as solvent in process step ii).
[0041] Process step ii) is preferably carried out for a period of between 10 and 30 minutes.
[0042] The amount of metal alkali salt in process step ii) is any one of the following weight ratios of metal alkali salt:fiber: 1:1, 1:10, 1:25, 1:50, 1:100.
[0043] Preferably, at least one acid is used in the neutralization process in process step iii). Preferably, the pH of the acid used will have a value in the range of 1 to 5. Preferably, the acid used will have a pH value of 3 or less. In a preferred case, the acid may be a mixture. At least one of the acid mixtures is an organic acid. Preferably, the organic acid in the acid mixture is at least 50% by weight.
[0044] At least one of the group propionic acid, acetic acid, sulfuric acid, hydrochloric acid, phosphoric acid, nitric acid, phosphoric acid, benzoic acid, nitric acid is used as acid for the neutralization process in process step iii).
[0045] Preferably, any acid is used as the acid in the neutralization process of process step iii).
[0046] The concentration of the acid preferably used in the neutralization process of process step iii) is in the range of 10% to 20% by weight.
[0047] In the process step neutralization process iii), the ratio of acrylic fiber:acid ranges from 1:1 to 1:150.
[0048] The neutralization process is carried out at any value within the temperature range of 40° C. to 60° C. Preferably, the neutralization process is carried out at any one of the following temperatures: 45° C., 50° C., 55° C., and 60° C.
[0049] Chlorides, acetates, sulfates, phosphates, carbonates of metals having an ionic value of +2 or +3 and included in periods 4 and 5 of the periodic table can be used as metal salts in process step iv).Preferably, salts of two or more metals can be used as metal salts.
[0050] Preferably, at least one of the chlorides, acetates or carbonates of transition metals having an ionic value (+2) is used as metal salt in process step iv).
[0051] Preferably, in process step iv) as metal salt zinc metal chloride, acetate, bromide or carbonate is used.
[0052] In process step iv), the metal salt is used at any value within the range of 8% to 20% by weight.
[0053] The ratio of acrylic fibres:metal salt in process step iv) ranges from 1:1 to 1:150.
[0054] According to the invention, process step iv) is carried out at any temperature within the range of 90-100°C.
[0055] According to the present invention, process step iv) is carried out for any value within the range of 15 to 30 minutes.
[0056] By applying the manufacturing process steps mentioned in the present invention, the production of polyacrylate fibers can be carried out for a period of 60 minutes to 120 minutes.
[0057] In the present invention, the term "tow" is the term given to a fiber form of an infinite number of filaments.
[0058] The production of polyacrylate in the current technology is carried out in a technology involving successive complex process steps in a reactor boiler with a discontinuous process system, which has low production volume and process efficiency, high costs, very long time (the production process steps available in the technology are 6 hours to 36 hours), and no reuse of waste and by-products after use is intended. Another innovative aspect of the present invention is that the production is carried out in a series of innovative continuous tank systems, with optimizations made in the production process steps. Thus, in the present invention, a process and production technology by modification of tow bands in a series of innovative continuous tank systems in succession along with optimized parameters for the production of polyacrylate fibers is developed, which presents technical solutions and advantages for the relevant technical field.
[0059] The polyacrylate fiber production of the present invention brings the following additions to the related art: A continuous industrial manufacturing process is provided; - Obtaining large quantities of polyacrylate fibers over a long period of time; Use chemicals that are less harmful to health, safety and the environment; - Reducing energy consumption; -reducing staffing needs; -reducing consumption of water and chemical inputs; · Reducing the carbon footprint during manufacturing.
[0060] In the current technology, the production of polyacrylates requires about 5 hours to complete the longest process step and about 1 hour to complete the shortest process step using a technology that includes a series of complex crosslinking, hydrolysis, neutralization, and metal complex formation process steps in a reactor boiler with a discontinuous batch process system. Therefore, the current production methods in the art do not allow continuous production in a tank chamber with a duration of 1 to 5 hours.
[0061] Current manufacturing methods in the art require the design of a tank that can accommodate 300 m of fiber for continuous production at a feed rate of 1 m / min when the process steps are carried out for about 5 hours. The investment cost of a tank of this configuration is not industrially feasible. In the present invention, the process including the process steps of complex crosslinking, hydrolysis, neutralization, metal complex formation forming a series of processes for the production of polyacrylate fibers can be carried out as a continuous production of fiber tow bands in a series of continuous tank systems, each step of which undergoes this process in the tank. In the production process of the present invention, the optimization of each successive chemical process step was studied, which results in a reduction in process time and takes into account the tank chamber dimensions, the number of tow bands, and the fiber extraction rate that are suitable for sustainable production. In this way, a production process of polyacrylate fibers that can be produced on an industrial scale is ensured.
[0062] Similar to WO 2008 / 128660 and EP 1026309, the polyacrylate manufacturing process in the technology of the present invention is carried out for a long period of time, such as 9 hours on average. Through the optimization of the present invention and the improvement of the polyacrylate manufacturing method, the process time has been reduced to 1 hour, and industrial manufacturing capacity has been achieved. The process of the present invention is different from the manufacturing process in the current technology, and its duration and consumption allow it to produce 9 tons of fiber instead of 1 ton of fiber. The manufacturing method of the present invention proposes an efficient manufacturing process with a reduction in process manufacturing time, development of a continuous manufacturing method instead of a discontinuous manufacturing method, reduction in energy consumption, and reduction in cycle costs.
[0063] In the current manufacturing method, boiler paint is produced in about 9 hours with a flote ratio of 1:4 to 1:6, and approximately 5 tons of water are used for each process step to produce 1 ton of fiber, resulting in a total water consumption of 25 tons. If the washing process steps are added, this value approaches 30 tons. Unfortunately, these amounts of water used in the manufacturing method of the current technology cannot be recycled and are disposed of as waste. The present invention is produced in a continuous manufacturing system by adding chemicals according to the consumption of chemicals, theoretically consuming no water, except for the moisture of the fiber tow belt and any amount of water evaporated due to process loss leakage. It can be seen that polyacrylate fiber, which is produced with a water consumption of 30 tons in the current manufacturing method, is produced with a water consumption of 1 to 2 tons in the present invention.
[0064] [Table 1]
[0065] The process for producing the polyacrylate fibers of the present invention also improves the carbon footprint of the process due to reduced water consumption, reduced energy consumption, and increased manufacturing capacity.
[0066] Comparing the current manufacturing method with the present invention, there are many different improvements, including manufacturing cost, duration, and carbon footprint.
[0067] The polymers forming the fibers are acrylonitrile polymers and may contain monomer units within the polymer chemical structure (CR1R2-CR3CN) and may also contain nitrile functional monomer units, where the structures R1, R2, and R3 may be H, alkyl (methyl, ethyl, propyl), aryl (phenyl). However, R1 and R2 may both be H and R3 may also be methyl and H. These polymer chemical structures (meth) may be acrylate, alkyl vinyl ether, or other types of comonomer units, or may be polyacrylonitrile and polymethacrylonyl, acrylonitrile-vinyl ester copolymers, and acrylonitrile polymer mixtures formed therewith. When the acrylonitrile polymer is a copolymer, such as a copolymer (tercopolymer, block copolymer), at least about 50% or more, or 60%, 70%, 80%, 90%, or 100% of the monomer units of the above chemical (CR1R2-CR3CN) structure.
[0068] The fibers developed by the manufacturing technology of the present invention can be short fibers (e.g., about 1 mm to about 1 cm in length) or long fibers (e.g., about 1 cm to about 1 m or more in length). At the same time, the diameter of the fibers can be about 0.7 to 50 dtex. If the diameter of the thin fibers in the fiber is less than 3 dtex, it may be easy for chemicals to penetrate into the fiber and polymer during crosslinking, hydrolysis, neutralization, and metal complex bonding. If the diameter of the thick fibers in the fiber is more than 7 dtex, chemical reactions may occur in a non-uniform manner throughout the fiber. However, depending on whether the size of the pore structure of the fiber is small, the crystal structure and crystallinity of the polymer forming the fiber, and the orientation of the polymer chains are more or less, the penetration of the chemical process occurring at each stage may be easier or more difficult. In fact, the core-shell structure may be formed by the modification of the polymer formed near the outer layer of the fiber. In such cases, these are obtained by modifying the properties of the resulting fiber and the outer layer of the fiber, and the modified fiber may impart flame retardancy, heat resistance, antifungal or antimicrobial properties, low heat transfer coefficient, high thermal insulation and moisture absorption, pH balance buffer function, acidity and base properties.
[0069] Polyacrylate fibers can be obtained from different forms of staple fibers, tows, tops, bumps, as well as from pores, threads, filament yarns, woven-nonwoven fabrics, and mixtures of at least one, two or more of acrylic fibers.Furthermore, in acrylic textile applications, the fabric can be, for example, socks or underwear, pieces of clothing such as outerwear, blankets such as fire blankets, curtains, textile mats, rugs, carpets.
[0070] Polyacrylate fibers can be produced starting from the form of acrylic fibers prepared using suitable heat, light, stabilizers, antimicrobial additives, antiviral additives, deodorant additives, biocidal additives, conductivity enhancers, antioxidants, pigments, plasticizers, and some additives that provide antifungal properties. These additives can be made into polyacrylate products by known methods, for example by dissolving the polymer in a solvent, combining the solution with the additives, and producing fibers by wet specific gravity technique. The fibers obtained are obtained from polyacrylate fibers using the production techniques detailed in the present invention. The polyacrylate obtained can be in the form of fibers, yarns, fabrics, etc. The products obtained can be used in many application areas of the textile sector, such as protective clothing, textile products for public transport, filtration materials, fireproof blankets, interior decoration, clothing (socks, underwear), textile applications for outdoor and indoor use, etc.
[0071] Polyacrylate fibers can be prepared by mixing with one or more suitable solutions of heat, light, stabilizers, antimicrobial additives, antiviral additives, deodorant additives, biocidal additives, conductivity enhancers, antioxidants, pigments, plasticizers, and some antifungal additives in the metal complex step, which is the last step of the known process steps, and can be produced by drying or fixing the fibers by heat treatment. These additives can be made into polyacrylate products by known methods, dissolving the additives in a suitable solvent and combining the solution with the additives, or producing fibers by wet injection molding techniques. The resulting polyacrylates can be in the form of fibers, yarns, fabrics, etc. Protective clothing, textile products for public transportation, filtration materials, fireproof blankets, upholstery, clothing (socks, underwear), textile products for outdoor and indoor use can be obtained from the resulting polyacrylate fibers.
[0072] During the manufacture of the polyacrylate fibers of the present invention, additional chemical compounds may be used to enhance the chemical and physical properties, such as flame retardancy, strength, and moisture resistance, of the resulting polyacrylate fibers.
[0073] As can be seen from the invention of Patent No. 5056358, the dyeing process of polyacrylate fibers can be carried out using cationic dyeing systems due to their chemical functional groups of carboxylate and carboxylic acid, but the color fastness and industrial application of the polyacrylate fibers after the process carried out in this way do not provide the desired technical properties. The inventors have determined that polyacrylate fibers, reagents, and pigment dyeing systems can show excellent performance in applicability and color fastness.
[0074] The scope of protection of the present invention is set forth in the appended claims and cannot be limited to the sample described in this detailed description. In view of the above facts, it is obvious that a person skilled in the art can provide similar embodiments without departing from the subject matter of the present invention.
[0075] test For the production of polyacrylate fibers, process steps known in the art are applied. The following process steps are provided: i. crosslinking the acrylic fibers with at least one crosslinking agent; ii. subjecting the acrylic fiber fibers that have been subjected to the crosslinking process to a hydrolysis reaction with at least one metal alkali salt; iii. after process step ii, subjecting the fibers to a neutralization reaction with at least one acid; iv. The fibers resulting from the neutralization process are complexed with at least one metal salt.
[0076] These process steps are tested by applying the development and optimization process of the present invention, and the results obtained are shared under this heading.
[0077] A hydrazine solution is used in the test as a cross-linking agent in process step i).
[0078] Hydrazine chemicals were used for cross-linking of the fibers and after application to the solution and fibers, the concentration on the fibers was analyzed by NIR spectroscopy. For the analysis, 0-80% reference solutions with known concentrations in the solution were prepared and a spectroscopic calibration was created. Calibration correlation R2=98. To analyze the cross-linked hydrazine on the fiber surface, solutions with known concentrations between 0-80% were prepared and applied separately at 107°C for 180 min. The obtained fibers were dried and analyzed by NIR spectroscopy and a calibration graph was created with a confidence range (R2>97%).
[0079] -Investigation of hydrazine fiber crosslinking rate In these tests, 30 g of acrylic fibers were prepared by mixing the media at 107°C, 200 rpm for various times as specified in the table, and crosslinking with a hydrazine solution at a concentration of 15 wt%. After each process step, the fiber form was washed with fiber water to remove chemical residues and dried overnight in an incubator at a temperature of 60°C.
[0080] As can be seen in detail in Table 2, the fibers were sampled for 180 minutes, and nitrogen elemental analysis and weight calculation revealed that 4.6% of hydrazine was attached to the fibers.
[0081] [Table 2]
[0082] Crosslinking process steps for acrylic fibers with hydrazine solution To investigate the relationship between hydrazine concentration in acrylic fiber and reaction time, 30 g of acrylic fiber was subjected to the concentration specified in Table 2, at a temperature of 107 °C, 200 rpm, and mixing medium. After each process step, the fiber was washed with water to remove chemical residues and dried overnight in an oven at a temperature of 60 °C. The amount of crosslinking on the fiber surface was then analyzed within the calibration standard range created by NIR spectroscopy. Based on the fact that the hydrazine solution forms 4.6% (w / w) crosslinks on the fiber, the required time is shown in Table 3.
[0083] [Table 3]
[0084] In test studies, it was determined that when the crosslinker had a concentration value of 60% by weight or greater in solution, the acrylic fibers did not exhibit desirable physical properties.
[0085] [Table 4]
[0086] - subjecting the acrylic fibres subjected to the crosslinking process to a hydrolysis reaction with at least one metal alkali salt; The hydrolysis reaction was carried out with sodium hydroxide, a metal alkali salt, at the concentrations specified in Table 5, for 30,5 g of fiber crosslinked at 4.6 wt.%, at a temperature of 105 °C, mixing the medium at 200 rpm. The mechanism of hydrolysis is realized in two stages, the first of which is recognized by the color change to dark red, and the second stage is judged by the color of the fiber becoming a complete light yellow. The completion of the reaction at this stage was detected by the time when the two-color transformation was completed. The obtained fibers were washed with hot water after each process step to remove chemical residues and dried overnight under incubator conditions at a temperature of 60 °C.
[0087] [Table 5]
[0088] In test studies, it was determined that when the metal alkali salt had a concentration of 30% or more by weight in solution, the acrylic fibers did not exhibit desirable physical properties.
[0089] -subjected to a neutralization reaction with at least one acid Neutralization of the polyacrylate converted from the acrylic fibers with acetic acid was carried out using acetic acid, a weak organic acid, at the concentrations specified in Table 6, at a temperature of 56 °C and mixing medium at 200 rpm. The neutralization of the fibers was monitored using FT-IR spectroscopy at 2900–3600 cm. -1 The neutralization of acetic acid concentration at different times is determined by monitoring the peaks of COONa chemical functional groups at a wide, wide range of wavelengths. The obtained fibers were washed with water to remove the acidic chemical residues, dried overnight under incubator conditions at a temperature of 60°C, and examined by FT-IR. The neutralization of acetic acid concentration at different times is shown in Table 6.
[0090] [Table 6]
[0091] In test studies, it was determined that when the acid had a concentration of 30% or more by weight in solution, the acrylic fibers did not exhibit desirable physical properties.
[0092] - complexing the resulting fibers with at least one metal salt; Polyvalent fibers can be obtained by neutralizing sodium polyacrylate fibers to prepare polycarboxylate fibers with carboxylic acid chemical groups to bind metal ions. In this process step, zinc ions were bound to the polymer by chelate complex coordination bonds at zinc concentrations specified in Table 7 by adding water as a suitable solvent for metal organic-inorganic salts and acid to increase ionization, and adjusting the solution to a pH range of 4.5-5 in the presence of weak acid at a mixing speed of 200 rpm, a temperature of 60 °C, and different times. The obtained fibers were inspected by washing with water to ensure that the washing did not remove excess zinc ions and acetate residues from the fibers, and drying at an incubator temperature of 60 °C.
[0093] [Table 7]
[0094] In test studies, it was determined that when the metal salt had a concentration of 30% or more by weight in solution, the acrylic fibers did not exhibit desirable physical properties.
[0095] [Table 8]
[0096] When the process steps shown in the manufacturing method of the present invention are produced by continuously applying chemical treatments in a series of continuous bath systems containing chemical solutions at 10 m / min and 0.01 m / min of fiber tow bands, the polyacrylate fibers have physical properties in the range of fiber thicknesses from 0.7 to 45 dtex and strengths from 12 to 35 cN / tex.
[0097] However, polyacrylate fibers can have low thermal conductivity, moisture retention properties of 10% or more, and fire resistance in the range of 30-40% LOI. In textile applications of acrylics obtained from mixtures of at least one, two or more of cotton, cellulose, polyester, nylon, fibers, yarns, fabrics, clothing, socks or underwear or outerwear, blankets and fire blankets, curtains, textile mats, rugs, carpets can be obtained from polyacrylate fibers and filament yarns.
Claims
1. A manufacturing method for producing polyacrylate fibers from acrylic textile products, in which the process environmental conditions and parameters are optimized, and the process reaction process time is shortened, thereby reducing the water consumption of the work intensity and energy consumption, thus becoming more environmentally friendly, and reducing the number of required personnel and unit production costs, and the method comprises: i. a process step of crosslinking the acrylic fibers with at least one crosslinking agent, said at least one crosslinking agent is a hydrazine or contains at least two amine functional groups therein or is a mixture thereof; wherein said at least one crosslinking agent is in the range of 35% to 50% by weight in at least one solution; Carrying out the process steps at a temperature anywhere in the range of -100°C to 110°C; - the acrylic fibre:crosslinking ratio is in the range of 1:1 to 1:300 by weight; ii. A process step of subjecting the acrylic fiber fibers that have been subjected to the crosslinking process to a hydrolysis reaction with at least one metal alkali salt, said at least one metal salt is present in the range of 8% to 20% by weight in said solution; Carrying out the process steps at a temperature anywhere in the range of -100°C to 110°C; - the ratio of acrylic fibres to metal alkali salt is in the range of 1:1 to 1:100; iii. After said process step ii), a process step of subjecting said fibers to a neutralization reaction with at least one acid, the acid is present in the solution in a range of 10% to 20% by weight; Carrying out the process steps at a temperature anywhere between -40°C and 60°C; - the acrylic fibre:acid ratio is in the range of 1:1 to 1:150; - the process step, wherein the acid is one of the acids having a pH value less than or equal to 3; iv. A process step in which the fibers resulting from the neutralization process are complexed with at least one metal salt, said at least one metal salt is present in said solution in a range of 8% to 20% by weight; Carrying out the process steps at a temperature anywhere between -90°C and 100°C; - the process step of: the acrylic fiber:metal salt ratio is in the range of 1:1 to 1:
150.
2. 2. The process according to claim 1, characterized in that each of the process steps i to iv) is carried out in a separate vessel or reactor, or, when the process step i) can be carried out in a separate vessel or reactor, the process steps ii), iii) and iv) are carried out sequentially in a series of separate continuous vessels or reactors.
3. 2. The process according to claim 1, characterized in that the process steps i to iv) are carried out continuously in a series of continuous tanks or reactors.
4. The manufacturing method according to any one of claims 1 to 3, characterized in that when applying a continuous manufacturing process step, the tow band has any value in the range of 0.01 m / min to 10 m / min.
5. Method according to any one of claims 1 to 4, characterized in that it is subjected to a cleaning process before, after or during said process steps i to iv).
6. 6. The process according to claim 5, characterized in that the temperature of the mixture of water and solvent used in the washing process is any one of the following temperatures: 20°C, 30°C, 40°C, 50°C, 60°C, 80°C.
7. 7. The process according to claim 1, characterized in that in process step i) it comprises as crosslinker at least one of the following compounds: -NH 2 - (CH 2 ) n -NH 2 , where n is one of the values 0, 2, 4, 6, 8; -NH 2 - (CH 2 ) n -NH-(CH 2 ) n -NH-(CH 2 ) n -NH 2 , where n is one of the values 0, 2, 4, 6, 8; -NH 2 - (CH 2 ) n -N-(-(CH 2 ) n -NH 2 )) (CH 2 ) n -NH 2 , where n is one of the values 0, 2, 4, 6, 8; -NH 2 - (CH 2 ) n -R-(CH 2 ) n -NH-(CH 2 ) n -NH 2 , where n is one of the values 0, 2, 4, 6, 8, and R is one of the following groups: CH, C.
8. The method according to any one of claims 1 to 7, characterized in that the crosslinking agent contains at least one of hydrazine, hexamethylenediamine, diethylenetriamine, tetraethylenetriamine, tetraethylenepentamine, bis-hexamethylenediamine, and tris(2-aminoethyl)amine compounds.
9. 9. The method according to claim 1, wherein the at least one crosslinking agent is dissolved in at least one solution, the solvent being at least one of the following compounds: water, methanol, ethanol, isopropanol.
10. The method according to claim 9, characterized in that the solvent is water and the concentration of the at least one cross-linking agent in the water ranges from 35% to 50% by weight.
11. Method according to any one of the preceding claims, characterized in that the process step i) is carried out for a duration of 15 to 30 minutes.
12. The method according to any one of claims 1 to 11, characterized in that the temperature of process step i) is any one of 100°C, 105°C, 106°C, 107°C, 108°C, 109°C and 110°C.
13. 2. The method according to claim 1, characterized in that in process step ii) the metal alkali salt is at least one of the following compounds: calcium hydroxide, magnesium hydroxide, calcium hydroxide, sodium hydroxide, calcium nitrate, magnesium nitrate, potassium nitrate, sodium nitrate.
14. 2. The process according to claim 1, characterized in that the solvent in process step ii) is at least one of the following organic solvents: water, methanol, ethanol, isopropanol.
15. 2. The method of claim 1, wherein said process step ii) is carried out for 15 to 30 minutes.
16. 2. The process according to claim 1, characterized in that in process step iii) the acid is at least one of the group: propionic acid, acetic acid, sulfuric acid, hydrochloric acid, phosphoric acid, nitric acid, phosphoric acid, benzoic acid, nitric acid.
17. 2. The method of claim 1, characterized in that the process step iii) is carried out at any one of the following temperatures: 45°C, 50°C, 55°C and 60°C.
18. 2. The method of claim 1, wherein said process step iii) is carried out for 15 to 30 minutes.
19. 2. The process according to claim 1, characterized in that the metal salt in process step iv) is at least one of the chlorides, bromides, acetates or carbonates of metals with ionic value (+2) or (+3).
20. 20. The method of claim 19, wherein the metal salt is at least one of a chloride, acetate, bromide, or carbonate salt of zinc metal.
21. 2. The method according to claim 1, characterized in that said process step iv) is carried out for a period of 15 to 30 minutes.
22. A method according to any one of the preceding claims, characterized in that the textile product obtained as a result of the application of the manufacturing process is treated with at least one of the following ingredients: cationic and non-ionic auxiliary chemicals, antistatic agents, lubricants and / or softeners.
23. A textile polyacrylate fiber or filament obtained by the manufacturing method according to any one of claims 1 to 22, having a CN / tex value of 12 or more, a size in the range of 0.7 to 45 dtex, a length in the range of 25 to 150 mm, an L.O.I value in the range of 30% to 40%, and a moisture retention property in the range of 10% or more.
24. 24. The polyacrylate fibre or filament of claim 23 having strength values in the range of 18 to 35 CN / tex.
25. 25. The polyacrylate fiber or filament according to claim 23 or 24, having antibacterial, antiviral, antifungal, antiodor properties, for use alone or in fiber blends with at least one of cotton, cellulose, polyester, nylon, textiles, clothing, socks, underwear or outerwear, blankets, fire blankets, curtains, fiber mats, rugs or carpets.
26. 25. Polyacrylate fibers or filaments according to claim 23 or 24, capable of absorbing moisture and water vapor and therefore exothermic, for use in the manufacture of yarns, fabrics, pieces of clothing, socks, underwear or outerwear, obtained alone or in fiber mixtures with at least one of cotton, cellulose, polyester, nylon.
27. Use of polyacrylate fibers or filaments, characterized in claims 23 to 25, for obtaining yarn fabrics, clothing, socks, underwear or outerwear, blankets, fire blankets, curtains, fiber rattan, rugs or carpets, obtained alone or in fiber mixtures with at least one of cotton, cellulose, polyester, nylon.